1982
DOI: 10.1128/jcm.15.6.1065-1073.1982
|View full text |Cite
|
Sign up to set email alerts
|

30 years of campylobacters: biochemical characteristics and a biotyping proposal for Campylobacter jejuni

Abstract: Several biochemical test systems were studied for their potential usefulness for the examination of strains of Campylobacter species. Most (81%) of the C. jejuni strains hydrolyzed sodium hippurate, but strains of C. fetus, C. sputorum, and C. fecalis did not. Some (46%) of the C. jejuni strains and all of the C. sputorum subsp. sputorum, C. sputorum subsp. bubulus, and C. fecalis strains hydrolyzed DNA, but the C. fetus and C. sputorum subsp. mucosalis strains did not. Strains of all species of Campylobacter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
49
0

Year Published

1983
1983
1992
1992

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(49 citation statements)
references
References 26 publications
0
49
0
Order By: Relevance
“…All individual strains used in this study were identified by their DCL number or number in the Penner serotyping system. C. jejuni, Campylobacter coli, Campylobacter fetus, and Campylobacter faecalis strains had been identified according to standard criteria (13,14). Most strains had been passaged multiple times on artificial media.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All individual strains used in this study were identified by their DCL number or number in the Penner serotyping system. C. jejuni, Campylobacter coli, Campylobacter fetus, and Campylobacter faecalis strains had been identified according to standard criteria (13,14). Most strains had been passaged multiple times on artificial media.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, major questions concerning the transmission of this agent and the pathophysiology of the infection it causes remain unanswered. Recent studies have shown that isolates from humans are heterogeneous in their biochemical (13) and serological (28) characteristics.…”
mentioning
confidence: 99%
“…However, the limited availability of adequate strain markers has curtailed studies aimed at elucidating the sources and modes of transmission of this organism. Procedures defining unique serotypes (1,19,26,28,30), biotypes (6,18), plasmid profiles (34), and chromosomal restriction patterns (7) have all been used to identify epidemic-causing strains. The usefulness of these techniques, however, has been limited by their complexity and limited availability.…”
mentioning
confidence: 99%
“…All Campylobacter sp. strains used in this study are shown in Table 1 and had been identified by standard criteria (7,9), passaged, and stored as previously described (16). The hippurate hydrolysis test was used to differentiate between C. jejuni and C. coli (7).…”
Section: Methodsmentioning
confidence: 99%
“…strains used in this study are shown in Table 1 and had been identified by standard criteria (7,9), passaged, and stored as previously described (16). The hippurate hydrolysis test was used to differentiate between C. jejuni and C. coli (7). Cultures were grown statically at 37°C for C. fetus or 42°C for C. jejuni and incubated in an atmosphere of 5% oxygen-10% carbon dioxide-85% nitrogen (9) for 48 h. The susceptibility of the test Campylobacter sp.…”
Section: Methodsmentioning
confidence: 99%